Efficacy assessment of an MVA vectored Rift Valley Fever vaccine in lambs. - Busquets, N; Lorenzo, G; López-Gil, E; Rivas, R; Solanes, D; Galindo-Cardiel, I; Abad, F; Rodríguez, F; Bensaid, A; Warimwe, G; Gilbert, S; Domingo, M; et al. (Elsevier, 2014)
The present study has evaluated the protection conferred by a single subcutaneous dose of a modified vaccinia virus Ankara (MVA) vectored vaccine encoding the Rift Valley Fever virus (RVFV) glycoproteins Gn and Gc in lambs. Three groups of six to seven lambs were immunized as follows: one group received the vaccine (termed rMVA-GnGc), a second group received an MVA vector (vector control) and a third group received saline solution (non-vaccinated control). Fourteen days later, all animals were subcutaneously challenged with 10(5) TCID50 of the virulent RVFV isolate 56/74 and vaccine efficacy assessed using standard endpoints. Two lambs (one from the vaccine group and one from the vector control group) succumbed to RVFV challenge, showing characteristic liver lesions. Lambs from both the vector control and non-vaccinated groups were febrile from days 2 to 5 post challenge (pc) while those in the rMVA-GnGc group showed a single peak of pyrexia at day 3 pc. RVFV RNA was detected in both nasal and oral swabs from days 3 to 7 pc in some lambs from the vector control and non-vaccinated groups, but no viral shedding could be detected in the surviving lambs vaccinated with rMVA-GnGc. Together, the data suggest that a single dose of the rMVA-GnGc vaccine may be sufficient to reduce RVFV shedding and duration of viremia but does not provide sterile immunity nor protection from disease. Further optimization of this vaccine approach in lambs is warranted.